Aromatic and Antiaromatic Cyclophane‐type Hexaphyrin Dimers. Issue 2 (4th January 2019) - Nakai, Akito; Yoneda, Tomoki; Ishida, Shin‐ichiro; Kato, Kenichi; Osuka, Atsuhiro
Abstract: A peripherally strapped [28]hexaphyrin takes a rectangular conformation and exhibits antiaromatic character. A cyclophane‐type dimer consisting of such [28]hexaphyrins was synthesized from hexakis(pentafluorophenyl) [26]hexaphyrin via SN Ar reaction with allyl alcohol, one‐pot intra‐ and intermolecular olefin metathesis under improved Hoveyda–Grubbs catalysis, and final reduction with NaBH4 . The cyclophane‐type structures of [26]‐ and [28]hexaphyrin dimers have been revealed by X‐ray analysis. Studies on the structural, optical, and electronic properties have led to a conclusion that there is no favorable electronic interaction between the two [28]hexaphyrin segments and thus no indication of 3D aromaticity. Abstract : Blinding the Cyclops : Cyclophane‐type [26]‐ and [28]hexaphyrin dimers have been synthesized from hexakis(pentafluorophenyl) [26]hexaphyrin via a six‐fold SN Ar reaction with allyl alcohol and subsequent olefin metathesis, and structurally well characterized by X‐ray analysis. In the latter dimer, there is no favourable interaction between the [28]hexaphyrin segments and hence no appearance of 3D‐aromaticity.